2017
DOI: 10.1186/s13046-017-0554-9
|View full text |Cite|
|
Sign up to set email alerts
|

RERG suppresses cell proliferation, migration and angiogenesis through ERK/NF-κB signaling pathway in nasopharyngeal carcinoma

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is a malignancy of the head and neck that is prevalent in Southeast Asia and southern China. Recent studies in epigenetics suggest that DNA methylation plays a pivotal role in the onset and progression of cancer. Combining the methyl-DNA binding domain capture technique and cDNA microarray analysis, we identified a unique hypermethylated gene, RERG (Ras-like estrogen-regulated growth inhibitor), that was down-regulated in NPC tissues. RERG is a tumor suppressor gene tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Additionally, the dual luciferase reporter assay validated that RERG was a target gene of miR-532-5p. In several cancer types, including breast cancer, RERG inhibits cell proliferation, migration, invasion and clonogenicity via the MAPK/ERK pathway (19,31). In the present study, cell proliferation and migration assays showed that RERG silencing could reverse miR-532-5p downregulation-induced cell proliferation and migration inhibition.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Additionally, the dual luciferase reporter assay validated that RERG was a target gene of miR-532-5p. In several cancer types, including breast cancer, RERG inhibits cell proliferation, migration, invasion and clonogenicity via the MAPK/ERK pathway (19,31). In the present study, cell proliferation and migration assays showed that RERG silencing could reverse miR-532-5p downregulation-induced cell proliferation and migration inhibition.…”
Section: Discussionsupporting
confidence: 56%
“…RERG was first identified as a ras-like, growth inhibitory protein induced by estrogen in breast cancer cells (18). Subsequent studies revealed that RERG was a negative regulator of multiple oncogenic pathways including the MAPK/ERK signaling in cancer cells (19,31). Furthermore, RERG was also regulated by histone deacetylases and miRNAs (19,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…46 Research has shown that the ectopic expression of RERG (Ras-like oestrogen-regulated growth inhibitor) in NPC cell lines resulted in a significant suppression of cell proliferation, invasion, and migration. 47 As a member of the RAS oncogene family, RAP2C has few reports on the development of cancer, which needs further study. Furthermore, MEF2C has recently been shown to play a role in the transcriptional control of cell cycle-related genes, and its degradation in mitosis contributes to G2/M checkpoint inactivation in growing myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected downregulation of RERG (RAS-like estrogen-regulated growth inhibitor) by DNA methylation in the cancer tissues. RERG-overexpressing cells showed significantly slower growth and less angiogenesis in tumor xenografts in nude mice [ 40 ]. DNA methylation occurs in Helicobacter pylori infection-related gastric cancer [ 41 , 42 ] and ulcerative colitis-associated colorectal cancer [ 43 ], indicating that DNA methylation is a key event of inflammation-related carcinogenesis.…”
Section: Epigenetic Alterations In Inflammation-related Carcinogenesimentioning
confidence: 99%